Weathering Products of a Dismantled Variscan Basement. Minero-Chemical Proxies to Insight on Cretaceous Palaeogeography and Late Neogene Palaeoclimate of Sardinia (Italy) - Mameli, Paola; Mongelli, Giovanni; Sinisi, Rosa; Oggiano, Giacomo (Frontiers in Earth Science, 2020)
This study compares, for the first time, the mineralogy and geochemistry of two residual-clay deposits in NW Sardinia (Nurra district) that formed at different times in tropical and sub-tropical climates. Both deposits represent palaeosols with deep-weathered residual profiles and overlie Mesozoic carbonate rocks that were deposited on the south European palaeomargin. The older alterite is Cenomanian–Turonian in age and grades upward into a horizon of karstic bauxite, whereas the younger unit occurs within alluvial deposits of Late Neogene age. The Cretaceous palaeosol represents the precursor of the overlying bauxite and formed from unknown sedimentary parent rocks. In contrast, the Messinian weathering products formed by alluvium that was sourced from the Variscan metamorphic basement. Chemical Index of Alteration values, REE fractionation index values, and the results of R-mode factorial analysis suggest a common initial weathering path and a common precursor for the deposits. However, the latter stages of weathering of the Cretaceous palaeosols resulted in lateritic alteration and bauxite production, whereas weathering of the Late Neogene, palaeosols produced 2:1 clay minerals under less extreme conditions. Comparison of these residual products constrains the parental material and weathering trends and allows insight into the relationship between palaeoclimate and regional/local palaeogeography of southern Europe during Upper Cretaceous and during Messinian.